2018
DOI: 10.1080/20550324.2018.1457764
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy resin nanocomposites with hydroxyl (OH) and amino (NH2) functionalized boron nitride nanotubes

Abstract: Hydroxyl (OH) and amino (NH 2) functionalized boron nitride nanotubes (f-BNNTs) were integrated into an epoxy resin (Epon828) to achieve improved mechanical properties. While raw BNNT-composites yielded the largest values for Young's modulus and appeared to be well mixed, f-BNNTs were found to provide a superior combination of mechanical properties yielding improvements in strain at failure, tensile strength and toughness that were not observed using raw BNNTs. In particular, an increase of 21% in Young's modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Some research upon BNNT-based nanocomposites, such as thermal conductivity improvement and mechanical reinforcement, was reported after the initial publications on the synthesis of the nanotubes , and reviewed in a number of papers. ,,, Only limited quantities of BNNTs were available, however, and any property enhancements reported initially were generally disappointing. The National Research Council Canada (NRC) has recently developed an industrially scalable plasma process for BNNT production chemistry, and polymer nanocomposites based upon these BNNTs have been shown to have more promising properties. …”
Section: Introductionmentioning
confidence: 99%
“…Some research upon BNNT-based nanocomposites, such as thermal conductivity improvement and mechanical reinforcement, was reported after the initial publications on the synthesis of the nanotubes , and reviewed in a number of papers. ,,, Only limited quantities of BNNTs were available, however, and any property enhancements reported initially were generally disappointing. The National Research Council Canada (NRC) has recently developed an industrially scalable plasma process for BNNT production chemistry, and polymer nanocomposites based upon these BNNTs have been shown to have more promising properties. …”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in view of the fact that the amine curing agent that was used, diethylenetriamine, contains mass NH 2 groups, we suggest the strengthening mechanism of the epoxy-CNF composite occurs via the chemical reaction between the CNF and active amide (amino CNF). Guan et al demonstrated that hydroxyl-and amino-functionalized boron nitride nanotubes, with epoxy nanocomposites, improve the strength due to the interaction of surface functional OH/NH 2 groups and/or covalent connections with epoxide rings [13]. Similarly, by using Fourier Transform Infrared Spectroscopy (FT-IR), Vijayan et al reported that active amide groups were formed by the chemical reaction between amine curing agents and CNF, leaving some unreacted amine groups [14].…”
Section: Resultsmentioning
confidence: 99%
“…Beside in situ hydroxylation in the BNNTs forming process [111,112], OH groups can be introduced by a pre-treatment in the presence of H 2 O 2 [33,[113][114][115][116], HNO 3 [117], NaOH [118], and other reactants [119,120] (see Fig. 16).…”
Section: Methods For Hydroxylated Bnntsmentioning
confidence: 99%
“…In situ hydroxylation Hydroxylated BNNTs can be directly obtained via a bottom-up approach [111,112]…”
Section: Bnntsmentioning
confidence: 99%